Gender Differences in Perception of Effective Vocabulary Teaching Strategies: An Exploratory Study of Thai University Students - Bancha, Woralak (Journal of International Studies, Prince of Songkla University, 2021)
The study aimed to investigate what vocabulary teaching strategies (VTS) Thai tertiary students perceived as effective and to examine if male and female students shared similar perceptions of VTS. The participants were 338 students from different programs at a government university in the south of Thailand. A mixed-method research design was adopted. A questionnaire was the main research instrument to collect the quantitative data concerning students’ perception and differences between male and female students’ perception of effective VTS. Then to gain an insightful data, the qualitative data derived from a semi-structured interview was employed. The main findings indicated that the students perceived all of the VTS as effective. The questionnaire results revealed pronouncing words with the highest mean score ( = 4.03) and using the board to note transcription ( = 3.43) with the lowest mean score. Concurrently, the interview data are in line with the questionnaire data emphasizing on some particular instructional strategies of cognitive, affective, and productive VTS. Furthermore, the two prime influential factors that have formed students’ perception were their learning experience and Thai culture. However, the findings showed no statistically significant gender differences in most of their perceptions (p < 0.05) except in the two major strategies of pronouncing words (t = -2.36, p = 0.02) and setting tasks of using words in sentences (t = -2.41, p = 0.02). The results of the study could guide university teachers in planning vocabulary instruction.